Analyzing CLIL Studies in Primary Education: Bibliometric analysis - Lazzat Yegizbayeva; Wilfried Admiraal; Makpal Zhazykova; Altyngul Mustoyapova; Almagul Akiyeva; Bakitgul Nurseitova; Asem Saimagambetova (Qubahan Academic Journal)
Content and Language Integrated Learning (CLIL) holds a pivotal role in fostering   English vocabulary acquisition among primary school students across various subjects. This study aims to undertake a comprehensive bibliometric analysis of English research articles spanning the past 16 years (2007-2023), focusing on CLIL implementation within primary education. Employing Boolean operators and wildcard symbols, we amalgamated pertinent keywords for querying the Scopus database. To facilitate bibliometric assessments, the Bibliometrix package within RStudio, in conjunction with Biblioshiny web applications, was harnessed. Our analysis encompassed tracking publication and citation patterns, identification of highly cited documents, assessment of prolific authors, nations, and universities, and recognition of influential journals. A dataset comprising 138 research articles was curated. Our investigation unveiled a consistent upward trajectory in both publication frequency and citation counts over the study's 16-year timeframe. Notably, the work by Fernandez-Sanjurio in 2019 emerged as the most cited paper. Foremost authors included Madrid D and Martinez Agudo JD, while the 'International Journal of Bilingual Education and Bilingualism' emerged as a leading publication venue. Among contributing institutions, the University of Cordoba and University of Granada featured prominently. The most prolific countries were Spain, China, and Australia, with notable collaboration occurring between Spain, China, and the United Kingdom. This study underscores the significant contributions of Spain in terms of authors, institutions, and citations, solidifying its role as a key contributor to the realm of CLIL research within primary education.